ANALISIS PERBANDINGAN KINERJA KEUANGAN MENGGUNAKAN METODE CAMEL PADA BANK BRI DAN BANK BNI PERIODE 2011-2015 - Kalendesang, Angelita Chyntia; Pangemanan, Sifrid S.; Gerungai, Natalia Y. T. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Bank as an intermediary institutions play a very important role in a country's economy. Therefore, the existence of a healthy bank is necessary, in order to achieve that goals banks have to be very careful in running their business and they also need special supervision include control from government through Central Bank which is known as Bank Indonesia. This research aims to examine and analyze the Assessment of the level of health of Commercial Bank, based on Bank Indonesia Regulation No. 13/1 / PBI / 2011, by using CAMEL (Capital, Asset, Management, Earnings, Liquidity) as its benchmarking tools. The ratio used includes financial ratio analysis such as CAR, KAP, NPM, ROA, BOPO and LDR. The object of study includes government-owned public banks listed on the IDX representing the entire population, but samples only taken from the financial statements of Bank BRI and Bank BNI during fiscal year 2011-2015, through research method of comparison of descriptive analysis to financial performance at both Bank (BRI & BNI), it can be concluded whether both of them are in the predicate healthy, healthy enough, less healthy or unhealthy. The results showed that both banks are equally healthy, while BRI have had better improvement of financial performance compared to BNI.Key words : Financial Performance, Financial Ratio, CAMEL Method, Commercial Bank Health.